Measurement of the ratios of branching fractions and. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We report an observation of the decay B(O)(S) --> D(-)(s)pi(+) in pp collisions at radical S = 1.96 TeV using 115 pb(-1) of data collected by the CDF II detector at the Fermilab Tevatron. We observe 83 +/- 11(stat) B(O)(s) --> D(-)(s)pi(+) candidates, representing a large increase in statistics over previous measurements and the first observation of this decay at a pp collider. We present the first measurement of the relative branching fraction Beta(B(O)(s) --> D(-)(s)pi(+))/Beta(B(0) --> D(-)(pi)(+)) = 1.32 +/- 0.18(stat) +/- 0.38(syst). We also measure Beta(B(+) --> D(0)pi(+))/Beta(B(0) -->D(-)pi(+)) = 1.97 +/- 0.10(stat) +/- 0.21(syst), which is consistent with previous measurements.